2007
DOI: 10.1007/s10571-007-9213-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term L-DOPA Treatment Causes Indiscriminate Increase in Dopamine Levels at the Cost of Serotonin Synthesis in Discrete Brain Regions of Rats

Abstract: (1) The treatment of choice for Parkinson's disease (PD) is 3,4-dihydroxyphenylalanine (L-DOPA) with peripheral decarboxylase inhibitor, but long-term therapy leads to motor and psychiatric complications. In the present study we investigated 5-hydroxytryptamine (5-HT) and dopamine concentrations in serotonergic and dopaminergic nuclei following chronic administration of L-DOPA to find whether the neurotransmitter synthesis in these brain areas are compensated. (2) Rats were administered L-DOPA (250 mg/kg) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 38 publications
1
35
1
Order By: Relevance
“…It could be concluded that, on the one hand, L -dopa therapy infl uences serotonin function and, on the other hand, that specifi c serotonergic treatment might improve adverse effects of L -dopa therapy. However, another animal study showed decreased 5-HT levels after long-term L -dopa treatment suggesting further necessity of distinguishing between different stages of PD (Borah and Mohanakumar 2007). Taylor et al (2009) showed symptoms of depression in mice with a reduction in vesicular monoamine transporter expression (VMAT2-defi cient), thus establishing a model of depression and other nonmotor symptoms in PD which also includes interaction between serotonergic and dopaminergic neurotransmission.…”
Section: Resultsmentioning
confidence: 99%
“…It could be concluded that, on the one hand, L -dopa therapy infl uences serotonin function and, on the other hand, that specifi c serotonergic treatment might improve adverse effects of L -dopa therapy. However, another animal study showed decreased 5-HT levels after long-term L -dopa treatment suggesting further necessity of distinguishing between different stages of PD (Borah and Mohanakumar 2007). Taylor et al (2009) showed symptoms of depression in mice with a reduction in vesicular monoamine transporter expression (VMAT2-defi cient), thus establishing a model of depression and other nonmotor symptoms in PD which also includes interaction between serotonergic and dopaminergic neurotransmission.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic L-dopa specifically affected the caudal extent of the dorsal DRN and the PFC, two brain regions involved in affective behaviors (Lowry et al, 2005(Lowry et al, , 2008Warden et al, 2012;Albert et al, 2014). The crosstalk between these two regions is involved in fear and anxiety responses in rats (Hashimoto et al, 1999;Bishop et al, 2004;Amat et al, 2005;Forster et al, 2006) and several preclinical and clinical studies propose that chronic L-dopa therapy for Parkinson's disease could result in mood disturbances, such as anxiety and depression (Damasio et al, 1971;Choi et al, 2000;Borah and Mohanakumar, 2007;Eskow Jaunarajs et al, 2010. These mood disturbances may be attributable to an underlying dysregulation of the monoaminergic systems within limbic regions as demonstrated in rats (Eskow Jaunarajs et al, 2012) and more recently in monkeys (Engeln et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown dopamine degradation and oxidation are toxic to serotonergic cells in culture (Stansley and Yamamoto, 2013) and to tryptophan hydroxylase (TPH), the rate-limiting enzyme for 5-HT synthesis (Kuhn and Arthur, 1998). Furthermore, rats treated chronically with L-dopa exhibit decreases in 5-HT tissue content in several brain regions (Borah and Mohanakumar, 2007;Eskow Jaunarajs et al, 2012) and decreased L-dopa-induced dopamine release by 5-HT terminals (Navailles et al, 2010a(Navailles et al, , 2011a. These reports suggest that chronic L-dopa leads to the accumulation of dopamine within 5-HT neurons that is detrimental to 5-HT system physiology and function.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, chronic L-dopa has been shown to reduce the number of 5-HT neurons in the DRN by similar oxidative mechanisms (Stansley and Yamamoto 2014). In addition to decreases in the number of 5-HT cell soma, chronic L-dopa depletes 5-HT content in several brain regions including the DRN, striatum, hippocampus, amygdala and PFC (Borah and Mohanakumar 2007; Navailles, Bioulac et al 2011; Eskow Jaunarajs, George et al 2012; Stansley and Yamamoto 2014). Importantly, proper 5-HT function in these regions is crucial for normal behavioral physiology (Lowry, Johnson et al 2005; Maier and Watkins 2005; Berger, Gray et al 2009; Monti 2011) such that 5-HT deficits in these areas result in impaired memory consolidation, executive cognitive dysfunction, fear, depression and anxiety (Lowry, Hale et al 2008; Soh, McGinley et al 2011; Euston, Gruber et al 2012; Izumi, Ohmura et al 2012).…”
Section: Introductionmentioning
confidence: 99%